PENGOLAHAN AIR LIMBAH BERWARNA INDUSTRI TEKSTIL DENGAN PROSES AOPs - Nugroho, Rudi; Mahmud, Ikbal (Jurnal Air Indonesia, 2005)
An experiment of advanced oxydation processes (AOPs) was applicated in textile wastewater treatment for color removal. The experiment was conducted in laboratory scale using ozon and hydrogen peroxide as oxidizing agents. The textile wastewater contains any organic and inorganic dyes that could not be effective treated by coagullation and and sedimentation as well as by conventional aerobic treatments. Result of the experiments concluded that the AOPs technologies could be applied effectively for removal of color. Addition of hydrogen peroxide with volume of 0.25 ml for 1 liter of wastewater exhibits the reaction. The reaction of AOPs for color removal was optimum at temperatur of 70oC. As higher as pH, the reaction become faster and the efficiency of color removal become higher. Ã‚Â Ã‚Â Key words: Ã‚Â advanced oxidation processes, color removal, hydrogen peroxide, ozon,Ã‚Â